Pre-eclampsia and febrile convulsions. Issue 8 (22nd July 2003) - Vestergaard, M; Basso, O; Henriksen, T B; Østergaard, J; Secher, N J; Olsen, J
Abstract : An association between pre-eclampsia and febrile convulsions has been reported, but the association may not be causal. We compared the risk of febrile convulsions in 14 974 children who had been exposed to pre-eclampsia in fetal life with that of 39 210 unexposed children. Children exposed to pre-eclampsia had a slightly increased risk of febrile convulsions, but the association was apparently caused by a shorter gestation in pre-eclamptic women.